2011
DOI: 10.1007/s00109-011-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

The imbalance of Th17/Th1/Tregs in patients with type 2 diabetes: relationship with metabolic factors and complications

Abstract: Immune disorders are linked to the development of type 2 diabetes (T2D) and its complications. The relationship of CD4(+)CD25(hi) T regulatory cells (Treg) and pro-inflammatory Th17 and Th1 subsets in T2D patients with metabolic disorders and complications need to be determined. The ratios of CD4(+)CD25(hi) Treg/Th17 cells and CD4(+)CD25(hi) Treg/Th1 cells, but not Th17/Th1 cells, were significantly decreased in T2D patients. The thymic output CD4(+)Foxp3(+)Helios(+) Tregs were normal but peripheral induced CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
170
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 42 publications
13
170
1
5
Order By: Relevance
“…Our idea was supported by Th1/Th2 ratios calculated as IL-2/IL-4, IL-2/IL-10, IFN-γ/IL-4, IFN-γ/ IL-10 which demonstrated a down-regulation of Th1 and up-regulation of Th2 profile in T2D patients. In fact, the Th2 profile exhibited by insulin-treated T2D patients is consistent with the anti-inflammatory profile of these patients [43][44][45] .…”
Section: Discussionsupporting
confidence: 79%
“…Our idea was supported by Th1/Th2 ratios calculated as IL-2/IL-4, IL-2/IL-10, IFN-γ/IL-4, IFN-γ/ IL-10 which demonstrated a down-regulation of Th1 and up-regulation of Th2 profile in T2D patients. In fact, the Th2 profile exhibited by insulin-treated T2D patients is consistent with the anti-inflammatory profile of these patients [43][44][45] .…”
Section: Discussionsupporting
confidence: 79%
“…As comparable to human studies, several animal experiments indicate that obesity promotes Th17 expansion and subsequent IL-17 production, exacerbating disease severity in murine models of multiple sclerosis and inflammatory bowel disease, both of which are representative Th17-related diseases as well as psoriasis 56 . Furthermore, it has been reported that IL-17A production from PBMCs are increased in type 2 diabetes patients compared with healthy controls 57 , and percentage of haemoglobin A1c, a common clinical marker of diabetes severity, is positively correlated with IL-17 production 54 . Thus, IL-17 is now increasingly recognized as a new mediator of adipose tissue metabolism and inflammation, indicating that psoriasis and obesity-related metabolic disorders have a common immunopathological basis in disease development.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Therefore, CNI agents are now believed to be necessary for prevention of allograft rejection but preferably with reduced doses. 7 Indeed, the imbalance of Th17/Treg has been shown to be associated with the development of inflammatory disorders [8][9][10] and allograft rejection. 11 Treg cells contribute to the induction and maintenance of tolerance of recipients to allografts, 12 while Th17 cells are important to mediate chronic allograft rejection.…”
Section: Introductionmentioning
confidence: 99%